2016
DOI: 10.1016/j.metabol.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological management of nonalcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) affects one-third of the population and two-thirds of patients with obesity or type 2 diabetes (T2DM). Its more aggressive form is known as nonalcoholic steatohepatitis (NASH) and is characterized by hepatocyte necrosis, inflammation and often fibrosis. The presence of fibrosis indicates a more aggressive course and may lead to cirrhosis. Premature mortality in NASH is related to both hepatic (cirrhosis and hepatocellular carcinoma) and extra-hepatic complications, larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 151 publications
4
68
0
5
Order By: Relevance
“…The newest class of medications, which treat both type 2 diabetes and obesity, is the GLP-1 analogues. Increasing evidence suggests that these medications are efficacious not only at reducing weight, but also at improving the comorbidities of obesity, including cardiovascular disease, non-alcoholic steatohepatitis [35,36] and overall mortality [3739]. Similar results to the most recent study, above, with liraglutide were demonstrated by this study group in the shorter-term.…”
supporting
confidence: 85%
“…The newest class of medications, which treat both type 2 diabetes and obesity, is the GLP-1 analogues. Increasing evidence suggests that these medications are efficacious not only at reducing weight, but also at improving the comorbidities of obesity, including cardiovascular disease, non-alcoholic steatohepatitis [35,36] and overall mortality [3739]. Similar results to the most recent study, above, with liraglutide were demonstrated by this study group in the shorter-term.…”
supporting
confidence: 85%
“…Further NASH leads to liver cirrhosis and hepatocellular cancer (Brandi et al, ). On the other hand, all individual affected with lipid accumulation in liver does not develops steatosis and NASH, confirms the multiple pathogenic events involved in NAFLD mediated hepatic damage (Barb, Portillo‐Sanchez, & Cusi, ). Furthermore, research reports shows that not all patients with steatosis or NASH extend liver inflammation and hepatocellular injury has led to the guess that diverse pathogenic events lead primarily to hepatic steatosis and secondly to hepatic injury.…”
Section: Introductionsupporting
confidence: 59%
“…Early studies in patients with T2DM suggested the potential benefit of GLP- 1RA from a reduction in liver enzymes 27. This reduction in plasma aminotransferases was also associated with a reduction in intrahepatic triglycerides proportional to the degree of weight loss28–30 or improvement in glycemic control 4.…”
Section: Glp-1ra For the Treatment Of Nafldmentioning
confidence: 99%